The Effect of STEM-Based Biology Learning on Thinking Skills Student Criticism of Environmental Pollution Material - Ardini, Wina; Wahidin; Samuel Agus Triyanto (UNIVERSITAS PGRI MADIUN, 2024)
This research aims to determine the effect of STEM-based biology learning onthe critical thinking skills of class X MIPA students at SMA Negeri 4Tasikmalaya on environmental change material. The population in this studywas all 5 classes of class educate. Data collection was carried out by providing13 questions describing critical thinking skills. The data analysis techniqueused was the independent t test with the help of the SPSS version 25 forWindows application with a significance level of 5%. Based on hypothesistesting, it was found that STEM-based biology learning had a significant effectof 0.01 or a significance value of <0.05 on critical thinking skills. In theresearch results, the experimental class was superior to the control class,seen from the average score achieved in critical thinking skills. So it can beconcluded that STEM-based biology learning influences students' criticalthinking skills on environmental change material.